2021
DOI: 10.3390/su132312949
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the Drivers of Italian Diversified Farms Efficiency: A Two-Stage DEA-Panel Tobit Analysis

Abstract: Farm diversification is an important phenomenon in agricultural systems and rural development in Europe, pursuing economic, social and environmental goals. For the sustainability of diversified farms, it is important to analyse some drivers affecting farm efficiency, for instance, socio-economic, technical and policy drivers. The efficiency performance of a panel of Italian farms practising other gainful activities in the period 2012–2017 was investigated and regressed against the drivers that mostly affects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In agriculture, input-oriented DEA models are used by some authors, because in this sector is very important the selection process of inputs is and in the end, outputs depend upon inputs (Toma et al, 2015;Imran et al, 2019;Zhang et al, 2016). If farmers have more control over the production outputs, then output-oriented DEA models for efficiency analysis are appropriate (Forleo et al, 2021;Romagnoli et al, 2021;Horvat et al, 2019;Kočišova, 2015;Bayyurt and Yılmaz, 2012).…”
Section: Within This Context Of Diversified Activities Thismentioning
confidence: 99%
“…In agriculture, input-oriented DEA models are used by some authors, because in this sector is very important the selection process of inputs is and in the end, outputs depend upon inputs (Toma et al, 2015;Imran et al, 2019;Zhang et al, 2016). If farmers have more control over the production outputs, then output-oriented DEA models for efficiency analysis are appropriate (Forleo et al, 2021;Romagnoli et al, 2021;Horvat et al, 2019;Kočišova, 2015;Bayyurt and Yılmaz, 2012).…”
Section: Within This Context Of Diversified Activities Thismentioning
confidence: 99%
“…The empirical evidence on how farm manager age impacts productivity indicates it may be sensitive to the regional context. For instance, Kimura and Sauer [1] found evidence of a negative relationship in Estonia and the Netherlands, but no statistically significant relationship in the case of England and Wales, as in Romagnoli, et al [16] for Italian farms. Work experience and formal education are both linked to greater productivity [17] and a threshold effect, identified by Sauer and Latacz-Lohmann [18], whereby a sufficient level of education is required to reap the productivity gains of investments in innovative technology.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…There is a general conclusion in the literature that adverse weather has a negative impact on productivity [7,32,33], explaining that farms, particularly those with high herd stocking density, are susceptible to climate shocks, such as extreme heat and increased temperatures, resulting in lower milk yield. Evidence from Kimura and Sauer [1] and Romagnoli, Giaccio, Mastronardi and Forleo [16] shows that farms located in environmentally disadvantaged areas in Estonia, England, Wales, and Italy are less productive, suggesting that natural conditions could limit productivity improvement.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Galluzzo argued that subsidies disbursed under only the second pillar of the CAP aimed to stimulate the rural development have not had any positive and clear effect on technical efficiency. On the contrary, Romagnoli et al (2021) argue that EU subsidies paid to less-favoured areas are pivotal for farms located in mountainous zones, with their use consequently impacting the technical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, through a twostage approach in the estimation of technical efficiency, as proposed as a theoretical framework by Wilson in 2011 andDaraio et al in 2018, it is possible to assess the effect of some environmental variables, such as the financial subsidies allocated through the CAP, on the technical efficiency in farms. Some recent studies conducted in Italy and Romania have used a two-stage analysis of technical efficiency in estimating the role of CAP subsidies using a non-parametric approach (Romagnoli et al, 2021;Galluzzo, 2021). The results showed that the effect of the financial subsidies disbursed through the first and second pillars of the CAP can diverge in the countries investigated.…”
Section: Introductionmentioning
confidence: 99%